SPATIAL VARIABILITY OF HYDRO-RELATED PHYSICAL PROPERTIES OF AL-RASHEED LOAM - Masood, Tareq K.; Salim, Salloom B. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
A field study was conducted on 2 hectare area at Al- Rashid district, south of Baghdad to analyze the spatial variability of saturated hydraulic conductivity (Ks), initial infiltration rate (IR), Porosity (F) and bulk density (BD). Based on measured BD values Rosetta software was used in this study to estimate water retention parameters, water content at θ33 and θ1500 kPa and unsaturated hydraulic conductivity at 33 kPa(k33), 100 kPa(k100) and  1500 kPa(k1500) according to Van Genuchten-Mualem model.  Measured and predicted data were analyzed both statistically and geostatistically and, the results showed a strong to moderate spatial dependence for the studied characteristics. The spatial correlation values (r2) were obtained with a spherical model for Ks, θ33, θ1500, k33, k100   and k1500, an exponential model for IR, and a Gaussian model for F and BD. Ks increased significantly with increasing of IR (r2 = 0.49**) and decreased with increasing of F and BD, IR increased with decreasing of BD (r2 = -0.326*) and BD increased with increasing of F (r2 = 0.989 **). In general the spatial distribution was moderately skewed (-0.5 to 0.5) for the studied characteristics with pronounced kurtosis (>2.5). The limit distance for the search radius to estimating spatial dependency varied from 29.9 m for BD to 105 m for IR.